The Act of Murder in QS. An-Nisa 92-94 - Darwin Wibowo Sihombing; Siti Hadijah (AT-TAFAHUM: Journal of Law, 2025)
Murder is one of the most serious crimes in Islam, directly related to the human right to life. This aims to exam in eview Islam regarding action murder based on Al-Qur'an Surah. Paragraph 92 until 94 in An-Nisa explain the difference between intentional and accidental murder, and analyze How values can be applied incontemporary life. The method that used is a qualitative research with an interpretive approach. Research shows that Islam very value values life, provides severe punishment for deliberate killing through the qishas system, and stipulates substitutes in the form of diyat and kafarat for accidental killing. The values contained in the sentence still relevant until currently, especially in help reject violence and fight for justicesocial.